2017
DOI: 10.1007/s11356-017-8395-9
|View full text |Cite
|
Sign up to set email alerts
|

Herbicides and trace metals in urban waters in Melbourne, Australia (2011–12): concentrations and potential impact

Abstract: Urban stormwater samples were collected from five aquatic systems in Melbourne, Australia, on six occasions between October 2011 and March 2012 and tested for 30 herbicides and 14 trace metals. Nineteen different herbicides were observed in one or more water samples from the five sites; chemicals observed at more than 40% of sites were simazine (100%), MCPA (83%), diuron (63%) and atrazine (53%). Using the toxicity unit (TU) concept to assess potential risk to aquatic ecosystems, none of the detected herbicide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Stormwater wetlands typically contain a mixture of contaminants, often at individual concentrations below those deemed biologically relevant (Allinson et al. ). Therefore, although frogs can discriminate and avoid unfavorable conditions (e.g., Vonesh and Buck ), their ability to do so may be reduced when they are exposed to complex mixtures of contaminants.…”
Section: Discussionmentioning
confidence: 99%
“…Stormwater wetlands typically contain a mixture of contaminants, often at individual concentrations below those deemed biologically relevant (Allinson et al. ). Therefore, although frogs can discriminate and avoid unfavorable conditions (e.g., Vonesh and Buck ), their ability to do so may be reduced when they are exposed to complex mixtures of contaminants.…”
Section: Discussionmentioning
confidence: 99%
“…; Allinson et al. ). These pesticides can adversely affect fish and invertebrates at low concentrations (Nebeker & Schuytema ; Amweg et al.…”
Section: Methodsmentioning
confidence: 97%
“…Likewise, diuron was dominantly found in interand sub-tidal deposits of GBR [134,135]. In Melbourne, Allinson et al [136] examined water quality of five different aquatic systems and found that many pesticides were present in high concentrations which included MCPA (83%), diuron (63%) and atrazine (53%). In another study, water screening from wetlands resulted in the detection of many harmful pesticides (simazine, atrazine and terbutryn) in high concentrations (Allinson et al [137]).…”
Section: Pesticide Contamination and Its Impacts On Global Ecosystemmentioning
confidence: 99%